2002
DOI: 10.1002/ajmg.10142
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOE ε2/ε3/ε4 and promoter gene variants with dementia but not cardiovascular mortality in old age

Abstract: The common apolipoprotein E (APOE) alleles epsilon2, epsilon3, and epsilon4 are associated with the risk of dementia and cardiovascular disease. Recently, two functional variants (- 219G/T and -491A/T) were identified in the promoter of the APOE gene that enable a further characterization of the role of the APOE locus in disease. We investigated the contribution of these APOE gene variants to dementia and cardiovascular mortality in old age using a population-based cohort of 648 subjects aged 85 years and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 47 publications
4
32
1
Order By: Relevance
“…Previously, the À219G/T polymorphism was associated with apoE plasma levels [Lambert et al, 2000;Stengard et al, 2002]. This SNP is in partial LD with the APOEE2/E3/E4 polymorphism [Fullerton et al;2000;Heijmans et al, 2002], and thus may have contributed to the association we observed.…”
Section: Discussioncontrasting
confidence: 42%
“…Previously, the À219G/T polymorphism was associated with apoE plasma levels [Lambert et al, 2000;Stengard et al, 2002]. This SNP is in partial LD with the APOEE2/E3/E4 polymorphism [Fullerton et al;2000;Heijmans et al, 2002], and thus may have contributed to the association we observed.…”
Section: Discussioncontrasting
confidence: 42%
“…Violation of the equilibrium was admitted in only four associations (two data sets) that we found to deviate. 21,24 Among the 163 disease-free controls (124 distinct data sets) where we found no statistically significant deviation from HWE, in three (three distinct data sets) 25,26 the articles reported that HWE was violated, and in 76 (54 distinct data sets) the articles correctly mentioned that HWE was not violated. For the rest of the papers either the authors have not reported anything about testing, or the results were not clear in their report.…”
Section: Reanalysis Of Hwe and Concordance With Reportingmentioning
confidence: 76%
“…In recent years, substantial evidence has confirmed that variants in the promoter of certain genes may underlie the pathogenesis of several neurological diseases, including Parkinson's disease [Wang et al, 2006], Huntington's disease [Coles et al, 1998], and AD [Fallin et al, 2001;Heijmans et al, 2002]. Very recent studies provide strong evidence that an APP promoter polymorphism, which has a higher transcriptional activity, over-expresses APP [Lv et al, 2008].…”
Section: Discussionmentioning
confidence: 96%